Intersectoral cooperation to increase HPV vaccine coverage: an innovative collaboration between Managed Care Organizations and state-level stakeholders - Natoshia Askelson; Grace Ryan; Laura Seegmiller; Alexander Preiss; Sara Comstock (Taylor & Francis Group, 2020)
In order to reduce disparities in human papillomavirus (HPV) vaccine coverage, intersectoral approaches are needed to reach vulnerable populations, including Medicaid enrollees. This manuscript describes a collaboration between Medicaid Managed Care Organizations (MCOs), the American Cancer Society, and a state health department in a Midwestern state to address HPV vaccination. Qualitative interviews (n = 11) were conducted via telephone with key stakeholders from the three participating organizations using an interview guide designed to capture the process of developing the partnership and implementing the HPV-focused project. Interviews were transcribed and coded using thematic analysis. Interviewees described motivation to participate, including shared goals, and facilitators, like pooled resources. They cited barriers, such as time and legal challenges. Overall, interviewees reported that they believed this project is replicable. Conducting this project revealed the importance of shared vision, effective communication, and the complementary resources and experiences contributed by each organization. Valuable lessons were learned about reaching the Medicaid population and groundwork was laid for future efforts to serve vulnerable populations and reduce health disparities. This work has significant implications for other organizations seeking to partner with large nonprofits, state health departments, MCOs, or others, and the lessons learned from this project could be translated to other groups working to improve vaccination rates in their communities.